Linear poly(ethylene imine)s: true molar masses, solution properties and conformation. Issue 46 (8th November 2017) - Perevyazko, Igor; Gubarev, Alexander S.; Tauhardt, Lutz; Dobrodumov, Anatoly; Pavlov, Georges M.; Schubert, Ulrich S.
Abstract : In-depth characterization of pharmaceutically relevant polymers plays a pivotal role in many areas, including nanoscience, gene therapy, analytical and polymer chemistry etc . Abstract : In-depth characterization of pharmaceutically relevant polymers plays a pivotal role in many areas, including nanoscience, gene therapy, analytical and polymer chemistry etc . Notwithstanding substantial efforts spent in this area, there are still unresolved challenges and one of the most demanding problems is the determination of absolute molar masses of a broad range of biocompatible cationic polymers. Hereby, we present a combined analytical approach for a distinct and self-consistent characterization of a series of linear poly(ethylene imine)s (PEIs) consisting of six in-house prepared PEIs (0.9 kDa < M theor < 250 kDa) and three commercially available linear PEIs (Polyscience labeled as 2.5 kDa, 25 kDa, and 250 kDa). The polymers were studied, in 0.2 M NaBr methanol, by the methods of molecular hydrodynamics: analytical ultracentrifugation, intrinsic viscosity and translational diffusion measurements. Absolute values of the molar masses were evaluated by the classical sedimentation-diffusion analysis resulting in the following range: 1.1 kDa < M < 13.9 kDa. It was demonstrated that the molar masses reported by the manufacturer, as well as theoretical and/or molar masses evaluated by common SEC analysis, are significantly overestimated. The complete set of Kuhn–Mark–Houwink–Sakurada scaling relations shows linear trends over the whole range of the molar masses, whilst the determined scaling indices virtually correspond to the homologous series characterized by a coil conformation ([ η ] = 0.255 × M 0.56 ; s 0 = 0.015 × M 0.48 ; D 0 = 994 × M −0.52 ). The conformational characteristics of LPEI, i.e. equilibrium rigidity (the Kuhn segment length) and the diameter of the PEI chains, were evaluated for the first time and constitute A = 1.9 ± 0.6 nm and d = 0.4 ± 0.2 nm, respectively. The presented self-sufficient analytical approach covers an important area of thorough polymer characterization by nowadays alternative but fundamental hydrodynamic methods allowing for complete structural and molecular analysis of almost any macromolecules in solution.